2014
DOI: 10.3109/10428194.2014.924115
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-26a-5p and microRNA-23b-3p up-regulate peroxiredoxin III in acute myeloid leukemia

Abstract: MicroRNAs (miRNAs) are small RNAs that regulate target gene expression. Using microarray-based miRNA expression profiling, we compared the miRNA expression in granulocytes from four patients with acute myeloid leukemia and four healthy controls. Thirty-four miRNAs were found to be differentially expressed, including 20 miRNAs that were up-regulated and 14 miRNAs that were down-regulated. The expression of selected miRNAs (miR-26a-5p and miR-23b-3p) was independently validated in 20 patients and 12 healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…Like in hepatoblastoma, AML and multiple myeloma, in this study, miR‐26a‐5p was also found downregulated in breast cancer, and low expression of miR‐26a‐5p predicted a negative index for the overall survival of breast cancer patients (Figure ). Overexpression of miR‐26a‐5p markedly inhibited breast cancer cell growth, and decreased the expression levels of cell cycle‐associated proteins (Figure ), which suggested that miR‐26a‐5p was a potential biomarker for breast cancer.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Like in hepatoblastoma, AML and multiple myeloma, in this study, miR‐26a‐5p was also found downregulated in breast cancer, and low expression of miR‐26a‐5p predicted a negative index for the overall survival of breast cancer patients (Figure ). Overexpression of miR‐26a‐5p markedly inhibited breast cancer cell growth, and decreased the expression levels of cell cycle‐associated proteins (Figure ), which suggested that miR‐26a‐5p was a potential biomarker for breast cancer.…”
Section: Discussionsupporting
confidence: 57%
“…MiR‐26a‐5p targeted the 3′‐untranslated regions of LIN28B and AURKA, and markedly inhibited their expressions, along with suppressing hepatoblastoma cell growth and clonality . In acute myeloid leukemia (AML), miR‐26a‐5p was found downregulated by a miRNA expression assay, and peroxiredoxin III (PrxIII) was identified as a direct target of miR‐26a‐5p . In this study, miR‐26a‐5p targeted ring finger protein 6 (RNF6) mRNA and inhibited its gene expression in breast cancer cells.…”
Section: Introductionmentioning
confidence: 81%
“…In the present study, overexpression of miRNA-23b-3p also increased oxidative stress in neurocyte cell by high-glucose. Jiang et al reported that microRNA-23b-3p up-regulate reactive oxygen species (ROS) and oxidative stress in acute myeloid leukemia (19).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of peroxiredoxin III caused by decreased miR-26a leads to a marked reduction in reactive oxygen species (ROS) in primary AML granulocyte samples ( 83 ). Growing evidence demonstrates that ROS plays a key role in regulating the balance between self-renewal and differentiation of HSCs ( 84 ).…”
Section: Emerging Roles Of Mirna Deregulation In the Pathogenesis Ofmentioning
confidence: 99%